A secure three-factor authentication scheme for wireless sensor networks using ECC. (18th May 2020) - Kumar, Devender; Singh, Harsh Kumar; Ahlawat, Chhahat
Abstract: Wireless Sensor Networks (WSNs) consist of small and low powered devices called as sensor nodes. They have been used in many areas like military, safety, health, agriculture, etc. One of the challenging issues in them is to provide the secure communication as the channels used are wireless. User authentication is a mechanism which is used to provide the secure communication in them. Here, we propose a three-factor authentication scheme for WSNs using ECC. We simulate it using the ProVerif tool for its formal security verification. We also discuss its informal security analysis to show that it is resistant to various known attacks. We evaluate the performance of our scheme in terms of security features, computational cost, communication cost and storage cost along with that of the existing related schemes. We show that it is more secured than the others schemes and has less communication cost.